2007
DOI: 10.1073/pnas.0708725104
|View full text |Cite
|
Sign up to set email alerts
|

Signal sequence mutation in autosomal dominant form of hypoparathyroidism induces apoptosis that is corrected by a chemical chaperone

Abstract: Autosomal dominant familial isolated hypoparathyroidism (AD-FIH) is caused by a Cys 3 Arg mutation (C18R) in the hydrophobic core of the signal peptide of human preproparathyroid hormone (PPTH). Although this mutation impairs secretion of the hormone, the mechanism by which one mutant allele produces the autosomal-dominant disease is unexplained. Using transfected HEK293 cells, we demonstrate that the expressed mutant hormone is trapped intracellularly, predominantly in the endoplasmic reticulum (ER). This ER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 37 publications
(37 reference statements)
0
48
0
1
Order By: Relevance
“…Chemical chaperone, such as PBA, is a low molecular weight compound known to stabilize protein conformation, improve ER folding capacity, and facilitate the trafficking of mutant proteins (48,49). To investigate the action of chemical chaperone, we first tested whether PBA protected against TM-induced ER stress as well as DNA fragmentation and PS externalization in Leishmania.…”
Section: Tm Promotes Cyt C and Endo G Release From Mitochondria And Smentioning
confidence: 99%
“…Chemical chaperone, such as PBA, is a low molecular weight compound known to stabilize protein conformation, improve ER folding capacity, and facilitate the trafficking of mutant proteins (48,49). To investigate the action of chemical chaperone, we first tested whether PBA protected against TM-induced ER stress as well as DNA fragmentation and PS externalization in Leishmania.…”
Section: Tm Promotes Cyt C and Endo G Release From Mitochondria And Smentioning
confidence: 99%
“…Thus, sustained accu- mulation of both unfolded proteins exceeded the threshold of ER stress required to induce apoptosis. ER stress-induced apoptosis has been implicated in several human disorders, including diabetes, Parkinson's disease, Alzheimer's disease, hypoparathyroidism, and also in 1 form of RP caused by the P23H rhodopsin mutation (17)(18)(19)(20)(21). That ER stress may be a pathogenic mechanism underlying retinal degeneration was also suggested by Colley et al, who found that NinaA, a photoreceptor specific homologue of cyclophilin, was required for export of Rh1 rhodopsin from the ER.…”
Section: Discussionmentioning
confidence: 74%
“…COS-7 and HEK-293 cells (American Type Culture Collection) were grown in Dulbecco's Modified Eagle's Medium (DMEM) containing 2 mM L-glutamine and 10% heat-inactivated FBS in a humidified atmosphere of 5% CO 2 at 37°C. The transfection procedure is as described earlier (20). All experiments were performed at 72-h post-transfection.…”
Section: Construction Of Mammalian Expression Vectorsmentioning
confidence: 99%
See 2 more Smart Citations